Direct Comparison of Mononucleated and Binucleated Cardiomyocytes Reveals Molecular Mechanisms Underlying Distinct Proliferative Competencies - Rebecca Windmueller; John P. Leach; Apoorva Babu; Su Zhou; Michael P. Morley; Aoi Wakabayashi; Nataliya B. Petrenko; Patrick Viatour; Edward E. Morrisey (Cell Reports, 2020)
Summary: The mammalian heart is incapable of regenerating a sufficient number of cardiomyocytes to ameliorate the loss of contractile muscle after acute myocardial injury. Several reports have demonstrated that mononucleated cardiomyocytes are more responsive than are binucleated cardiomyocytes to pro-proliferative stimuli. We have developed a strategy to isolate and characterize highly enriched populations of mononucleated and binucleated cardiomyocytes at various times of development. Our results suggest that an E2f/Rb transcriptional network is central to the divergence of these two populations and that remnants of the differences acquired during the neonatal period remain in adult cardiomyocytes. Moreover, inducing binucleation by genetically blocking the ability of cardiomyocytes to complete cytokinesis leads to a reduction in E2f target gene expression, directly linking the E2f pathway with nucleation. These data identify key molecular differences between mononucleated and binucleated mammalian cardiomyocytes that can be used to leverage cardiomyocyte proliferation for promoting injury repair in the heart. : Windmueller et al. develop a strategy to separate mononucleated and binucleated cardiomyocytes and examine transcriptional differences acquired as the two subsets diverge during the neonatal period. Binucleation is associated with silencing of proliferation genes and upregulation of maturation genes. Genetic loss of Ect2 links binucleation to the Rb/E2f pathway. Keywords: cardiac regeneration, mononucleated, binucleated, cardiomyocyte, proliferation, Rb, E2f, Ect2, heart, development